MicroRNA-22 Regulates the Pro-inflammatory Responses and M1 Polarization of Macrophages by Targeting GLUT1 and 4-1BBL - Young Jun Kang (Journal of Immunology Research, 2023)
Many microRNAs (miRNAs) are selectively expressed in mammalian immune cells and have been linked to immune responses in host defense and autoimmune disease. In macrophages, miRNAs regulate cell metabolism by repressing the expression of genes such as transcription factors, enzymes, and metabolism-related molecules, as well as the expression of genes that impact inflammatory responses and phenotype determination. Previous studies showed that miR-22 plays a role in a variety of biological processes, such as cancer cell growth, cell survival, and cell expansion. In CD4 + T cells of inflammatory bowel disease patients, miR-22 is upregulated and regulates inflammasome-mediated responses. However, it has not yet been determined how miR-22 contributes to the activation of innate immune cells. In this study, we identified a mechanism of toll-like receptors- (TLR-) dependent miR-22 induction that regulates the downstream signaling pathway linking inflammatory responses and macrophage polarization. MiR-22 is induced via TLR-signaling, which regulates the induction of Slc2a1 (glucose transporter 1 and Glut1) and Tnfsf9 (tumor necrosis factor 9, 4-1BB ligand, and 4-1BBL) mRNAs that contribute to sustained inflammatory responses and the polarization of macrophages. Our observations support further efforts to explore a potential therapeutic strategy using miR-22 for the modulation of excessive macrophage activation for the treatment of inflammatory diseases.